Phase II study of ERC1671 plus bevacizumab versus bevacizumab plus placebo in recurrent glioblastoma: interim results and correlations with CD4+ T-lymphocyte counts. (29th August 2018) - Bota, Daniela A; Chung, Jinah; Dandekar, Manisha; Carrillo, Jose A; Kong, Xiao-Tang; Fu, Beverly D; Hsu, Frank PK; Schönthal, Axel H; Hofman, Florence M; Chen, Thomas C; Zidovetzki, Raphael; Pretto, Chrystel; et al.
Aim: ERC1671 is an allogeneic/autologous therapeutic glioblastoma (GBM) vaccine – composed of whole, inactivated tumor cells mixed with tumor cell lysates derived from the patient and three GBM donors.Methods: In this double-blinded, randomized, Phase II study bevacizumab-naive patients with recurrent GBM were randomized to receive either ERC1671 in combination with granulocyte-macrophage colony-stimulating factor (GM-CSF) (Leukine ® or sargramostim) and cyclophosphamide plus bevacizumab, or placebo plus bevacizumab.Interim results: Median overall survival (OS) of patients treated with ERC1671 plus bevacizumab was 12 months. In the placebo plus bevacizumab group, median OS was 7.5 months. The maximal CD4 + T-lymphocyte count correlated with OS in the ERC1671 but not in the placebo group.Conclusion: The addition of ERC1671/GM-CSF/cyclophosphamide to bevacizumab resulted in a clinically meaningful survival benefit with minimal additional toxicity.